2012
DOI: 10.1002/jsfa.5766
|View full text |Cite
|
Sign up to set email alerts
|

Universal primers for species authentication of animal foodstuff in a single polymerase chain reaction

Abstract: These primers permit the identification of most animal taxa employed in human nutrition, from invertebrates such as molluscs to higher vertebrates, distinguishing between species of the same genus. The short fragment amplified within the 16S rDNA exhibits phylogenetic value and could be considered universal based on the wide taxonomic range assayed. The primers are easy to use and accessible for laboratories with a modest budget, as well as being valuable for consumer information and to reveal food fraud.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 35 publications
0
25
0
1
Order By: Relevance
“…5 and Table 2). More animal species were found from DNA than from labels with Horreo et al 18 primers, whereas for plants it was the opposite, with more plants and fruits stated in the labels than found from DNA with Han et al 19 primers.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…5 and Table 2). More animal species were found from DNA than from labels with Horreo et al 18 primers, whereas for plants it was the opposite, with more plants and fruits stated in the labels than found from DNA with Han et al 19 primers.…”
Section: Resultsmentioning
confidence: 89%
“…Since candies are highly processed their DNA is likely degraded, 17 and therefore we targeted short species-specific sequences. For animal species we employed the primers 16S-HF 5 ′ -ATAACACGAGAAGACCCT-3 ′ and 16S-HR 5 ′ -CCCRCGGTCGCCCCAAC-3 ′ developed by Horreo et al 18 that amplify an 80-122 base pair (bp) fragment within the 16S rRNA gene. PCR reaction was performed with: 5 μL DNA extraction from the candy (from less than 0.0005 ng μL −1 to 0.328 ng μL −1 ), 0.125 μL Taq polymerase from the PCR Core Kit Plus, polymerase solution with Mg 2+ 1×, 0.5 μL of each primer (10 μmol L −1 ), 0.5 μL dideoxynucleotides (dNTPs with U), 0.5 μL Uracil glycosylase and bidistilled water up to 25 μL of total volume.…”
Section: Dna Extraction Quantification Pcr Amplification and Sequenmentioning
confidence: 99%
“…Nonphylogenetic signal may become dominant and yield incongruent, yet statistically highly supported phylogenomic trees (Jeffroy et al, 2006), and hence it could be useful to know the existence of one gene in each group of species (such as family or genus) that would be representative of its evolution, being especially useful to construct the phylogenetic relationships of this group. In this sense, Horreo et al (2012) have found recently a very short fragment of the 16S rDNA (around 120 bp) with some phylogenetic value.…”
Section: Introductionmentioning
confidence: 91%
“…In this sense, Horreo et al . () have found recently a very short fragment of the 16S rDNA (around 120 bp) with some phylogenetic value.…”
Section: Introductionmentioning
confidence: 99%
“…Horreo et al (2013) designed universal primers based on the nucleotide sequences of the 16S rRNA gene of 40 animal species that belonged to seven different taxonomic classes (Actinopterygii, Gasteropoda, Cephalaspidomorphi, Amphibia, Chondrichthyes, Aves, and Mammalia), obtaining PCR amplicons ranging from 80 to 125 bp. Sequencing analyses confirmed the differences among species and, although very short, they were considered very informative and enabled clustering of samples into their respective taxonomic group.…”
Section: Pcr-sequencingmentioning
confidence: 99%